Pelatihan Pembuatan Pelembut Pakaian di Pondok Pesantren Baitul Qur’an Rumbai Pekanbaru Sebagai Peluang Wirausaha - Nanda Herru, Yoan De; Anggrena D. Ritonga; Rahma Joni (JDISTIRA - Jurnal Pengabdian Inovasi dan Teknologi Kepada Masyarakat, 2024)
The Baitul Qur'an Islamic boarding school has carried out training activities in making clothes softener as an opportunity for entrepreneurship. The implementation method consists of two stages, namely preparation and implementation. The training participants were 41 students at the Baitul Qur'an Islamic boarding school. The results of the first stage, namely preparation, participants will be explained the materials used, their uses and how to make the fabric softener used in this training. Participants who initially did not know the ingredients, uses and how to make clothes softener finally learned the process. This conclusion was obtained from the results of the pre-test and post-test carried out during the training. For the manufacturing stage, the participants softeners to make clothes softeners well